Contact and local services in Andalusia: the contextual effect of place of residence - Navarro Yañez, Clemente J.; Mateos Mora, Cristina (Cuadernos de Trabajo Social, 2012)
Contact between the public and public administration is a form of long-term, relevant participation since it assumes the transmittal of requests and information about problems and services in cities, making, in effect, the citizenry part of public service provision. By presenting a representative survey of the Andalusian population taken in 2010, this article analyzes the frequency of contact of the Andalusian public, their socio-political characteristics and their reasons for the contact. This permits a view of the extent of this rarely studied participatory phenomenon, as well as its causes. In particular, this article seeks to show the existence of contextual effects based on the size of the municipality and its participation in the dynamics of urban areas.